Gestão e avaliação de cursos de especialização lato sensu: estudo em instituições de ensino superior para construção de um modelo de acreditação educacional - Tahim, Ana Paula Vasconcelos de Oliveira (2018)
Result of the new relationships in the world of work, educational evaluation goes beyond its initial object of action, reaching new roles. All levels of education are evaluated and accredited, but the lato sensu specializations have not received the same attention, only being evaluated in a timely manner and internally by the Institutions of Higher Education (HEI). Understanding that these courses emerge in the various HEIs with the character of continuing training and insertion into the world of work, thus, also need to be evaluated as well as accredited. Therefore, the main concern of this thesis is: how to accredit postgraduate courses, specifically the lato sensu specialization in education, in order to contribute to professional training of excellence? The purpose of this study is to elaborate an evaluation model for a specialization course, observing its accreditation, as well as the quality of the educational issues that permeate the need for an accreditation. The structure of this study will be based on the methodological space of De Bruyne (1977); for the methodological organization, the theoretical categories were defined a priori: course management and evaluation and educational accreditation, and for the strategy of data collection, interviews and questionnaires via Skipe and WhatsApp, as well as for data analysis the use of Atlas IT. The relevance of this research is perceived in the reflective possibility of improvement over the management of the specialization course, its impact on professional training and its autonomous role on co-responsibility, thus, using evaluation as a tactic of continuous improvement of the actions developed and in the decisions about the progress of accreditation. It is considered that the consultation and listening to the study subjects greatly contributed to the mapping of essential structures (LIMA, 2005) culminated in accreditation. The theme also needs to be better explored in HEIs, since evaluation and accreditation are still confused, greater clarification allows the empowerment of processes.